Control of gene expression through regulation of the TATA-binding protein - Pugh, B.F.
The assembly of transcription complexes at eukaryotic promoters involves a number of distinct steps including chromatin remodeling, and recruitment of TATA-binding protein (TBP)-containing complexes, the RNA polymerase II holoenzyme. Each of these stages is controlled by both positive and negative factors. In this review, mechanisms that regulate the interactions of TBP with promoter DNA are described. The first is autorepression, where TBP sequesters its DNA-binding surface through dimerization. Once TBP is bound to DNA, factors such as TAFII250 and Mot1 induce TBP to dissociate, while other factors such as NC2 and the NOT complex convert the TBP/DNA complex into an inactive state. TFIIA antagonizes these TBP repressors but may be effective only in conjunction with the recruitment of the RNA polymerase II holoenzyme by promoter-bound activators. Taken together, the ability to induce a gene may depend minimally upon the ability to remodel chromatin as well as alleviate direct repression of TBP and other components of the general transcription machinery. The magnitude by which an activated gene is expressed, and thus repeatedly transcribed, might depend in part on competition between TBP inhibitors and the holoenzyme for access to the TBP/TATA complex.
Keywords: GENE EXPRESSION; GENERAL TRANSCRIPTION FACTORS; TATA-BINDING PROTEIN; TAFS; TBP; TFIID